Fabrication, Illumination Dependent Electrical and Photovoltaic Properties of Au/Bod-pyr Schottky Diode - Ongun, Onur; Emrullahoğlu, Mustafa; Taşcı, Enis; Emrullahoğlu, Mustafa; Akın, Ummuhan; Tuğluoğlu, Nihat; Eymur, Serkan (Springer, 2021)
4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based BOD-Pyr compound was synthesized according to the literature and HOMO and LUMO energies of the BOD-Pyr were calculated by DFT/B3LYP/6-311G(d,p) method using on Gaussian 09 W. Au/BOD-Pyr/n-Si/In Schottky diode were fabricated using thermal evaporation and spin coating technique. The electronic and photovoltaic properties of Au/BOD-Pyr/n-Si/In diode have been investigated by current-voltage (I-V) measurements at dark and under various illumination intensities. The calculated ideality factor and barrier height of the diode in dark were found to be 2.84 and 0.75 eV, respectively. These parameters were also obtained under 100 mW/cm(2) illumination level as 1.55 and 0.87 eV, respectively. The values of open-circuit voltage and short circuit current density were obtained as 0.26 V and 0.56 mA/cm(2) under the illumination level of 100 mW/cm(2). These all findings suggest that Au/BOD-Pyr/n-Si/In diode can be used as photodiode in optoelectronic applications.
Keywords: Schottky diodes